Constraint identification and analysis in African small ruminant systems - Ngategize, P.K. (International Livestock Centre for Africa, 1989)
A review of the economic role of small ruminants and their production constraints is presented. Approaches to small ruminant constraint identification and analysis are identified. Levels of production economics analysis are suggested and examples of economic or statistical models given. Simulation analysis is identified as a powerful tool in constraint identification and analysis due to its robustness.